rWTC-MBTA: autologous vaccine prevents metastases via antitumor immune responses - Ye, Juan; Wang, Herui; Medina, Rogelio; Chakraborty, Samik; Sun, Mitchell; Valenzuela, Alex; Sang, Xueyu; Zhang, Yaping; Uher, Ondrej; Zenka, Jan; Pacak, Karel; Zhuang, Zhengping (Journal of experimental & clinical cancer research, 2023)
BACKGROUND: Autologous tumor cell-based vaccines (ATVs) aim to prevent and treat tumor metastasis by activating patient-specific tumor antigens to induce immune memory. However, their clinical efficacy is limited. Mannan-BAM (MB), a pathogen-associated molecular pattern (PAMP), can coordinate an innate immune response that recognizes and eliminates mannan-BAM-labeled tumor cells. TLR agonists and anti-CD40 antibodies (TA) can enhance the immune response by activating antigen-presenting cells (APCs) to present tumor antigens to the adaptive immune system. In this study, we investigated the efficacy and mechanism of action of rWTC-MBTA, an autologous whole tumor cell vaccine consisting of irradiated tumor cells (rWTC) pulsed with mannan-BAM, TLR agonists, and anti-CD40 antibody (MBTA), in preventing tumor metastasis in multiple animal models. METHODS: The efficacy of the rWTC-MBTA vaccine was evaluated in mice using breast (4T1) and melanoma (B16-F10) tumor models via subcutaneous and intravenous injection of tumor cells to induce metastasis. The vaccine's effect was also assessed in a postoperative breast tumor model (4T1) and tested in autologous and allogeneic syngeneic breast tumor models (4T1 and EMT6). Mechanistic investigations included immunohistochemistry, immunophenotyping analysis, ELISA, tumor-specific cytotoxicity testing, and T-cell depletion experiments. Biochemistry testing and histopathology of major tissues in vaccinated mice were also evaluated for potential systemic toxicity of the vaccine. RESULTS: The rWTC-MBTA vaccine effectively prevented metastasis and inhibited tumor growth in breast tumor and melanoma metastatic animal models. It also prevented tumor metastasis and prolonged survival in the postoperative breast tumor animal model. Cross-vaccination experiments revealed that the rWTC-MBTA vaccine prevented autologous tumor growth, but not allogeneic tumor growth. Mechanistic data demonstrated that the vaccine increased the percentage of antigen-presenting cells, induced effector and central memory cells, and enhanced CD4+ and CD8+ T-cell responses. T-cells obtained from mice that were vaccinated displayed tumor-specific cytotoxicity, as shown by enhanced tumor cell killing in co-culture experiments, accompanied by increased levels of Granzyme B, TNF-α, IFN-γ, and CD107a in T-cells. T-cell depletion experiments showed that the vaccine's antitumor efficacy depended on T-cells, especially CD4+ T-cells. Biochemistry testing and histopathology of major tissues in vaccinated mice revealed negligible systemic toxicity of the vaccine. CONCLUSION: The rWTC-MBTA vaccine demonstrated efficacy in multiple animal models through T-cell mediated cytotoxicity and has potential as a therapeutic option for preventing and treating tumor metastasis with minimal systemic toxicity.
Keywords: TLR agonists; Humans; rWTC-MBTA vaccine; Metastasis; melanom; Female; Mannans; imunologická paměť; antigeny CD40; lidé; mannany; CD40 Antigens; zvířata; myši; Antigens, Neoplasm; Mice; antigeny nádorové; Breast Neoplasms; ženské pohlaví; Mannan-BAM; Melanoma; protinádorové vakcíny; T-cell cytotoxicity; Cancer Vaccines; nádory prsu; Animals; Immunologic Memory